Protein reviews. Volume 18 - Atassi, M. Zouhair (Springer, 2017)
The aim of the Protein Reviews is to serve as a publication vehicle for review articles that focus on crucial current vigorous aspects of protein structure, function, evolution and genetics. The volumes will appear online before they are published in a printed book. Articles are selected according to their importance to the understanding of biological systems, their relevance to the unravelling of issues associated with health and disease or their impact on scientific or technological advances and developments. The chapters in volume 18 are authored by experts in the field. They deal with aspects of structure and/or biological activity of selected proteins. The chapters review current research of the following topics: the Mechanism of channel gating and regulation of the activity of calcium-activated chloride channel ANO1, Structure and function of the two-component cytotoxins of Staphylococcus aureus, Membrane Fusion and Infection involving the influenza virus hemagglutinin, The impact of arrhythmogenic mutations through the structural determination of the L-type voltage-gated calcium channel, Discussion of some open questions pertaining to histone post-translational modifications and nucleosome organization in transcriptional regulation, Regulation of the extracellular SERPINA5 (protein C inhibitor) penetration through cellular membranes, Coding of Class I and II aminoacyl-tRNA synthetases, Nephrin phosphorylation in diabetes and chronic kidney injury, The structure-forming juncture in oxidative protein folding and the events in the ER, The polyspecificity of anti-lipid antibodies and its relevance to the development of autoimmunity. This volume is intended for research scientists, clinicians, physicians and graduate students in the fields of biochemistry, cell biology, molecular biology, immunology and genetics.
Includes index.
Keywords: Proteins.; elektronické knihy; electronic books